Considerations for Investing in the Secondary Stock Market - Khadka, Ajaya Kumar; Khadka, Srijana (Management Dynamics, 2022)
The primary purpose of this research is to examine major aspects of investing. This study employed a causal-comparative research approach to assess correlation and regression, using data collected from 385 respondents involved in secondary market support via a non-probability sampling frame and a purposive sample method. Investment choice is the dependent variable, whereas firm image, accounting information, personal financial demands, and herding are the independent variables. The correlation and regression analyses found high statistical significance between corporate image and 12investment choice. At the same time, there is a positive correlation between the investment choice and each independent variable. The herding factor is a subsequent significant variable for the investment decision. At the same time, the importance of meeting one’s financial obligations is far less substantial. The results of a one-way ANOVA demonstrated that gender, age, and educational background had no modest influence on investing activities. The research concluded that investors base their decisions on a firm’s image; thus, businesses must devise strategies to improve their public image. There is much room for investigating more compact elements that determine behavior.